2004
DOI: 10.1124/jpet.103.059824
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Agonist Activity of Selected Ligands of the Cysteinyl-Leukotriene Receptor 1

Abstract: Cysteinyl leukotrienes (CysLTs) are associated with several inflammatory processes, including asthma. Due to this association, considerable effort has been invested in the development of antagonists to the CysLT receptors (CysLT 1 R). Many of these molecules have been shown to specifically interact with CysLT 1 R, but little is known about their impact on the conformation of the receptor and its activity. We were especially interested in possible inverse agonist activity of the antagonists. Using a constitutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Moreover, phenidone and BW755C, dual inhibitors of LOX/COX pathways, decrease kainic acid-induced seizures, suggesting the involvement of leukotrienes in this effect [10,11]. In line with this view, Rehni and Singh (2011) have shown that montelukast, a CysLT 1 receptor inverse agonist [12] and1,2,3,4-tetrahydroisoquinoline, regarded as a LTD 4 synthetic pathway inhibitor, dose-dependently suppress the development of kindled seizures, as well as pilocarpine-induced spontaneous recurrent seizures [13]. Similarly, Liu and colleagues (2014) have shown that zileuton, a 5-LOX inhibitor, decreases spike-wave discharges in pilocarpine epileptic rats [14].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, phenidone and BW755C, dual inhibitors of LOX/COX pathways, decrease kainic acid-induced seizures, suggesting the involvement of leukotrienes in this effect [10,11]. In line with this view, Rehni and Singh (2011) have shown that montelukast, a CysLT 1 receptor inverse agonist [12] and1,2,3,4-tetrahydroisoquinoline, regarded as a LTD 4 synthetic pathway inhibitor, dose-dependently suppress the development of kindled seizures, as well as pilocarpine-induced spontaneous recurrent seizures [13]. Similarly, Liu and colleagues (2014) have shown that zileuton, a 5-LOX inhibitor, decreases spike-wave discharges in pilocarpine epileptic rats [14].…”
Section: Introductionmentioning
confidence: 70%
“…wakefulness) from basal and after treatment periods were identified in EEG recording and divided in 15 s segments and a 4 s epoch from each segment (without artifacts) was used to carry out the power analysis by the conversion into frequency domain by fast Fourier transformation (FFT) method. The resultant power values displayed for each frequency were grouped into 5 bands represented by delta (0.1-4 Hz), theta (4-8 Hz), alpha (8-12 Hz), beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and gamma . For power analysis of decomposed waves, the power sum from all frequencies (0.1-80 Hz) was considered as 100%.…”
Section: Electrocorticographic Recording Analysis and Seizure Evaluamentioning
confidence: 99%
“…It has been demonstrated that montelukast, possibly as an inverse agonist, reduces the intracellular level of phosphatidyl inositol triphosphate and diminished the intracellular calcium flux essential for a number of functions in eosinophils. 28 Intracellular calcium is essential for cell migration. [29][30][31] However, further studies are needed to better understand the role of calcium in protease activation or expression.…”
Section: Discussionmentioning
confidence: 99%
“…By quantifying two important signaling molecules of the inflammatory response, the present study showed the effectiveness of the pharmacologically classified as cysLT receptor antagonist zafirlukast to attenuate NO induction during the delayed hypersensitivity reaction in the rat conjunctiva, without inducing significant alterations either in the basal histamine content or in the nitrite levels in the lavage fluid in the unchallenged eye. Although it has been shown that zafirlukast can block LT-induced NO release in other tissues [19,20], this study aimed neither at correlating NO release with LT levels, nor at determining the molecular mechanisms of the cysLT receptor antagonists, which may act as inverse agonists [21] and/or as modulators of inducible NOS via pathways independent of cysLTs [22]. This first report on the interaction between cysLT-receptor antagonists and NO in the conjunctiva may provide the lead for the evaluation of the leukotrienic component in the treatment of ocular hypersensitivity disorders.…”
Section: Discussionmentioning
confidence: 99%